2019
DOI: 10.1590/1807-3107bor-2019.vol33.0069
|View full text |Cite
|
Sign up to set email alerts
|

Does traumatic occlusal forces lead to peri-implant bone loss? A systematic review

Abstract: Observational studies have indicated that crestal bone level changes at implants are typically associated with clinical signs of inflammation, but still mechanical overload has been described as possible factor leading to hard-tissue deficiencies at implant sites without mucosal inflammation. The aim of this paper was systematically review the literature regarding the possible effect of traumatic occlusal forces on the peri-implant bone levels. Literature search was conducted using PubMed, Scielo and Lilacs, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 24 publications
0
29
0
3
Order By: Relevance
“…This is where a marked increase in stress was noted. It seems, therefore, that the risk of loosening or even damage to these elements is greater than the disintegration of the implant or peri-implantitis [ 40 , 41 ]. The conducted research confirmed the reports of other authors that the greatest load occurs in the distal parts of the bar retention [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is where a marked increase in stress was noted. It seems, therefore, that the risk of loosening or even damage to these elements is greater than the disintegration of the implant or peri-implantitis [ 40 , 41 ]. The conducted research confirmed the reports of other authors that the greatest load occurs in the distal parts of the bar retention [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Occlusal overloading has been reported as the main responsible for bone loss, which also contributes for the high prosthetic failures rates suggesting that excessive loading is more harmful (1,9,30). For this reason, the load used in the study was an axial force in order to create a physiological environment and isolate that influence of treatment modalities in the bone tissue biomechanics.…”
Section: Discussionmentioning
confidence: 99%
“…Few clinical papers have shown a correlation between overload and peri-implant inflammation, and no direct link has been found in animal studies [ 59 ]. However, excessive occlusal force may cause implant fracture [ 60 ], resulting in rapid bone resorption around the implant.…”
Section: Peri-implantitismentioning
confidence: 99%